Asymptomatic detection of SARS‐CoV‐2 among cancer patients receiving infusional anti‐cancer therapy. (28th October 2021) - Shaya, Justin; Cabal, Angelo; Nonato, Taylor; Torriani, Francesca; Califano, Joseph; Lippman, Scott; Sacco, Assuntina; McKay, Rana R.
Abstract: Background: Little is known regarding the rate and clinical outcomes of asymptomatic carriers of SARS‐CoV‐2 among patients with cancer. Detection of asymptomatic carriers is important in this population given the use of myelosuppressive and immunomodulating therapies. Understanding the asymptomatic carrier rate will help to develop mitigation strategies in this high‐risk cohort. Methods: Retrospective cohort analysis of an asymptomatic screening protocol which required patients receiving infusional anti‐cancer therapy to undergo a symptom/exposure screen and SARS‐CoV‐2 PCR testing 24–96 h prior to their infusion. The primary outcome of this analysis was the rate of asymptomatic SARS‐CoV‐2 infection. Secondary outcomes included the rate of COVID‐19‐related hospitalization and mortality and delays in oncologic therapy. Results: Among a cohort of 2691 cancer patients who underwent asymptomatic screening, 1.6% ( N = 43/2691) of patients were found to be SARS‐CoV‐2 positive on asymptomatic screening. 11.6% ( N = 5/43) of the cohort ultimately developed COVID‐19‐related symptoms. Four patients required hospitalization for complications of COVID‐19 infection. No patient died from COVID‐related complications. 97.7% ( N = 42/43) had their anti‐cancer therapy delayed or deferred with a median delay of 21 days (range: 7–77 days). Conclusions: Overall, among a cohort of active cancer patients receiving anti‐cancer therapy, an asymptomatic SARS‐CoV2 PCR‐based screening protocol detected a small cohort of asymptomatic carriers. The majority of these patients remained asymptomatic on long‐term follow‐up and outcomes were much more favorable compared to previously described outcomes of cancer patients with symptomatic COVID‐19 infection. Abstract : Little is known about the rate of asymptomatic SARS‐CoV‐2 carriers among cancer patients. Here, we examined a cohort of active cancer patients who underwent asymptomatic SARS‐CoV‐2 PCR screening prior to their infusion therapy. We found a low rate of asymptomatic carriers (1.6%) among this cohort and this asymptomatic cohort had favorable longterm infectious outcomes.